IMPLEMENTASI PROGRAM PERBIKAN GIZI MASYARAKAT KATEGORI BALITA BERSTATUS GIZI KURANG DI KELURAHAN SUNGAI MALANG KABUPATEN HULU SUNGAI UTARA - reno affrian (UPT Publikasi Dan Pengelolaan Jurnal Universitas Islam Kalimantan MAB Banjarmasin, 2018)
Based on Basic Health Research (RKD) and Toddler Operations in North Hulu Sungai Utara, nutritional problems are less increasing in the last three years, 2015 less than 17.32% malnutrition, 2016 less than 20.54% and nutrition prevalence less by 24%. Less nutritional problems in Hulu Sungai Utara Regency are included in the categorization of serious public health problems due to nutritional prevalence above 20%. mapping of the poor urban village region donated the most under-five children under five, namely 537 children under five. Based on the results of the research that the implementation of nutrition improvement program for under-fives under-nutrition category in urang sub-district in the northern river upstream district has not run well enough, it is known from: 1. Environmental aspect in the form of community economic environment and family care pattern, 2. Target group, some program implementers are not yet fully aware of the targets set by the government nationally, 3. Program activities, activities carried out only as routine activities ie immunization activities and postal services yando, 4.Pengelolaan Management and Pengawasa, not fully run well it diliat still lack inter-sectoral coordination, factors affecting nutrition improvement program for under-fives under-fives category in poor urban village influenced by several factors 1. Policy Size and Objectives 2. Resources, 3. Characteristics of implementing agents, 4. Attitudes / implementers, 5. Intercommunications organization and activities of the implementer, 6. Economic, social and political environment.